Adult autism. - Low, Fiona. (2010)
There are at present 30,000 individuals with autism in Singapore. Of this, about 18,500 of them are adults over the age of 19. However, services for the adult autism population is inadequate. This feature takes an in depth look at the dire straits adult autism care is in now.